The Reluctant Fundamentalist - Mohsin Hamid (Karachi Oxford University Press, 2016)
At a cafe table in Lahore, a bearded Pakistani converses with a suspicious, unnamed American stranger. As dusk deepens into night, he begins the tale that has brought them to this fateful meeting, a tale of love, disenchantment, and the abandonment of a high-flying life in New York...
Keywords: Pakistani Americans -- Race discrimination -- Self-perception